2020
DOI: 10.1097/ijg.0000000000001592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Atmospheric Pressure Changes on Dynamic Contour Tonometry and Goldmann Applanation Tonometry in Normal Individuals: A Pilot Study

Abstract: Précis: Intraocular pressure (IOP) measurement differences with Goldmann applanation tonometry (GAT) and dynamic contour tonometry (DCT) are affected by atmospheric pressure inside a hyperbaric chamber. Purpose: To compare IOP measurements obtained with GAT and DCT in 22 normal individuals at different atmospheric pressures simulated in a hyperbaric chamber. Methods: The IOP of both eyes of 22 healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Albis-Donado et al 15 more recently evaluated the changes in IOP with exposure to increase atmospheric pressure within a hyperbaric chamber with both Goldman applanation tonometry and dynamic contour tonometry. Their study found that with increasing atmospheric pressure, IOP was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Albis-Donado et al 15 more recently evaluated the changes in IOP with exposure to increase atmospheric pressure within a hyperbaric chamber with both Goldman applanation tonometry and dynamic contour tonometry. Their study found that with increasing atmospheric pressure, IOP was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…However, if negative pressure is mostly distributed Albis-Donado et al 15 more recently evaluated the changes in IOP with exposure to increase atmospheric pressure within a hyperbaric chamber with both Goldman applanation tonometry and dynamic contour tonometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research of IOP in hyperbaric chambers is limited to a 2020 study from Albis-Donado et al, which compared IOP measurements from AP and dynamic contour tonometry (DCT) at varying ATM of 1, 1.1, 1.2, and 1.25. They found that DCT was influenced by ATM changes in an inverse relationship to AP [ 15 ]. RB, therefore, may potentially present an avenue by which researchers can overcome some of the critical technical difficulties of using AP, and by extension DCT, to measure IOP within hyperbaric chambers.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the literature regarding altitude-related alterations in IOP and ocular hemodynamics is much less clear. While several studies have indicated IOP may increase with altitude [6,[12][13][14][15][16][17][18][19][20][21][22], many have also found an opposing decrease in IOP with altitude [7,8,[23][24][25][26][27][28][29][30][31][32]. Additionally, studies have shown that short-term exposure to high altitudes can alter the retinal microcirculation in young, healthy subjects secondary to hypoxic endothelial dysfunction [33].…”
Section: Introductionmentioning
confidence: 99%